SIMULASI DISTRIBUSI TEKANAN INJEKSI PADA RESERVOIR MENGGUNAKAN METODE FINITE DIFFERENCE - Jamaluddin Jamaluddin; Nuruddin Kafy El-Ridlo; Hamriani Ryka; Maria Maria (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2020)
The modeling of reservoir injection pressure distribution is very important to perceive reservoir management, especially in estimating the pushing mechanism. The modeling of reservoir injection pressure distribution was carried out by applying the analytic equation of fluid flow to the porous media of Darcy's law and transformed to a finite difference numerical equation which then used Neumann boundary conditions. The parameters used in the modeling were: permeability, average layer thickness, porosity, acceleration of gravity, viscosity, and area’s width. Based on the results of modeling, the injection pressure distribution area decreased as injection pressure rate increased. This decrease occurred due to an imbalance between the volume of reservoir fluid produced by the volume of water from the aquifer that replaced the reservoir, caused emptying. From the results of the modeling the amount of oil production, obtained from the remaining oil reserves to the initial oil acquisition in the reservoir after the process of pressure maintenance, could be found.